Developing effective collaborations: Learning from our practice - Jo Kennedy; Ian McKenzie; Joette Thomas (Administrative Sciences, 2019)
In this article we explore the challenges inherent in developing effective interorganizational relationships in the context of supporting the integration of health and social care in Scotland. We begin by outlining the context of health and social care integration and the nature of the program. We then describe the theories that underpinned our approach and outline in detail how the approach worked in practice in one area. We go on to discuss our reflections on six practices participants found helpful in creating the conditions necessary for effective collaboration. Finally, we end by reflecting on our learning.
Keywords: 350; collaboration; leadership; integration; shared purpose; accountability